Glued Endocapsular Hemi-Ring Segment for Sutureless Trans-Scleral Fixation of the Capsular Bag and Its Contents - Soosan Jacob; Amar Agarwal; Athiya Agarwal (Delhi Journal of Ophthalmology)
The glued endocapsular ring, designed by the author (SJ), is a new device aimed at fibrin glue assisted sutureless trans-scleral fixation of a subluxated cataract/ IOL. This eliminates suture related complications while providing better stability of the bag intra-operatively as well as in the long term post-operatively. This device allows easier surgery and avoids cumbersome, complicated needle passes through the anterior chamber. Intra-operative adjustment and if required, readjustment of IOL centration is possible and easy unlike sutured rings and segments. The fibrin glue allows a hermetic seal of the flap over the exteriorized haptic. The device is made of PVDF and is available as hemi-ring as well as smaller segments.